Weekly Paclitaxel in the Adjuvant Treatment of Breast Cancer - Sparano, Joseph A. (2008)
BACKGROUND: We compared the efficacy of two different taxanes, docetaxel and paclitaxel, given either weekly or every 3 weeks, in the adjuvant treatment of breast cancer. METHODS: We enrolled 4950 women with axillary lymph node–positive or high-risk, lymph node–negative breast cancer. After randomization, all patients first received 4 cycles of intravenous doxorubicin and cyclophosphamide at 3-week intervals and were then assigned to intravenous paclitaxel or docetaxel given at 3-week intervals for 4 cycles or at 1-week intervals for 12 cycles. The primary end point was disease-free survival. RESULTS: As compared with patients receiving standard therapy (paclitaxel every 3 weeks), the hazard ratio for disease-free survival was 1.27 among those receiving weekly paclitaxel (P = 0.006), 1.23 among those receiving docetaxel every 3 weeks (P = 0.02), and 1.09 among those receiving weekly docetaxel (P = 0.29) (with a hazard ratio >1 favoring the groups receiving experimental therapy). As compared with standard therapy, weekly paclitaxel was also associated with improved survival (hazard ratio, 1.32; P = 0.01). An exploratory analysis of a subgroup of patients whose tumors expressed no human epidermal growth factor receptor type 2 protein found similar improvements in disease-free and overall survival with weekly paclitaxel treatment, regardless of hormone-receptor expression. Grade 2, 3, or 4 neuropathy was more frequent with weekly paclitaxel than with paclitaxel every 3 weeks (27% vs. 20%). CONCLUSIONS: Weekly paclitaxel after standard adjuvant chemotherapy with doxorubicin and cyclophosphamide improves disease-free and overall survival in women with breast cancer. (ClinicalTrials.gov number, NCT00004125.)